Evaluation Study of Using Blockchain Technology in Supply Chain Management Processes - KIRBAÇ, GÖKHAN (Abant İzzet Baysal Üniversitesi Sosyal Bilimler Enstitüsü, 2021)
Nowadays, processes of information technologies have become important for supply chain management. Also, the supply chain processes become even more complex. In order to solve this complexity, businesses manage supply chain processes with many systems. Blockchain has a number of advantages for not only finance but also supply chain. The aim of this research is to serve a descriptive use case for using blockchain technology in the supply chain processes. In-depth interviews are conducted with supply chain managers and blockchain technology professionals. Architectural design processes of blockchain technology in the supply chain are determined. Lastly, Analytic Hierarchy Process was applied to the main characteristics of blockchain. This study is a descriptive study that serves as a roadmap for firms that want to use blockchain technology in their supply chain processes.Keywords: Supply Chain Management, Blockchain Technology, Blockchain Challenges, Logistics Processes, Analytic Hierarchy Process (AHP).
Tedarik Zinciri Yönetimi Süreçlerinde Blok Zinciri Teknolojisinin Kullanılmasına Yönelik Değerlendirme Çalışması
Keywords: Supply Chain Management; Blockchain Technology; Blockchain Challenges; Logistics Processes; Analytic Hierarchy Process (AHP)